Electronic Marketing and its Impact on the Corporate Entrepreneurship: A Field Study at Yemeni Private Universities in the Capital Municipality of Sana'a - Jamal Al-Deen, Ahmed Qassim; Ghawth, Ghaleb Abdullah (Journal of Economic, Administrative and Legal Sciences, 2025)
The current study aimed to investigate the impact of electronic marketing on the institutional entrepreneurship in private universities in Sana’a City، and to identify the extent to which these universities practice electronic marketing and achieve institutional entrepreneurship. The study followed a descriptive analytical research method. the study sample included nine private universities that have been established for more than ten years and their strategic visions included the entrepreneurial dimension. Data were collected using a questionnaire of 220 items distributed to the managers of the higher and middle management as well as to the electronic marketing specialists in the targeted universities. The study findings showed that there was a positive impact of various dimensions of the electronic marketing such as electronic product، electronic promotion، electronic distribution، and electronic pricing on the institutional entrepreneurship in the targeted private universities in Sana’a City. Among these dimensions، the dimension of the electronic product had the highest impact on the institutional entrepreneurship while the electronic pricing dimension had the least impact. The study recommended that the universities should achieve advanced levels of entrepreneurship and continuously improve the of electronic marketing through aligning the design of electronic educational products with the clients' needs. Therefore، the universities can obtain new opportunities in the labor market، and achieve integration among the various dimensions of the electronic marketing with particular focus on the electronic product. Moreover، the private universities should provide peer-reviewed electronic journals to publish academic research، organize online scientific conferences and to be pioneers in implementing new ideas included in the related research and studies. Additionally، continuously evaluation should be conducted for their programs and services through their websites to enhance and develop the strategies، programs and educational services.
Keywords: Electronic Marketing; Institutional Entrepreneurship; Yemeni Private Universities